PENGEMBANGAN PROGRAM BIMBINGAN BELAJAR BERDASARKAN MOTIVASI BELAJAR PESERTA DIDIK SMA: Studi Deskriptif terhadap Peserta Didik Kelas XI SMAN 1 Cimalaka Tahun Ajaran 2012-2013 - Barkah, Ari (2013)
Motivation to learn is the change in energy or impetus from within (internal) or outside of (external) individuals to undertake activities that can change behavior for the better as a result of the experience already gained. This study is based on problems experienced by learners who have low motivation in the learning process, making it appear maladapted behaviors of learners that will lead to stagnation in the learning process that leads to boredom, loss of creativity, have low morale, even until the decline in student achievement. The approach taken is a descriptive study of the Class XI students of SMAN 1 Cimalaka. The data was collected using a questionnaire measuring instruments. Results of a study of class XI students of SMAN 1 Cimalaka show that most learners have a high motivation to learn as many as 116 people (84.7%), 19 students (13.9%) had the motivation to learn in the medium category and 2 people (1.46%) students had very high motivation to learn, which means that most of the students have made learning as needs to be done to be able to actualize themselves optimally with the indicated achievement to learn that according to maximum potential. Recommendations are given to (1) Teacher guidance and counseling: expected to cooperate with all school personnel involved as stakeholders and publish comprehensive guidance programs, (2) further research: more depth in every aspect of the motivation to make learning as a requirement that must be met by learners so as to actualize themselves in the form of learning achievement can best be achieved in accordance with the potential of learners, and (3) Research data can be recommended for counseling and guidance courses to learn. Student achievement on every aspect and indicators contained in the motivation to learn is developed based on the achievement of requirements can be used as a reference or benchmark to determine learning achievement by learners. Keyword : Academic Guidance Program, Learning Motivation